19.5k views
1 vote
−2/9−(−1/3÷3/5) ,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,

User Mark Smith
by
5.2k points

1 Answer

4 votes

Answer:

Explanation:


\\ \sf ( - 2)/(9) - ( ( - 1)/(3) / (3)/(5))


\\ \sf = ( - 2)/(9) - ( ( - 1)/(3) * (5)/(3) )


\\ \sf = ( - 2)/(9) - ( (- 5))/(9)


\\ \sf = ( - 2)/(9) + (5)/(9)


\\ \sf = ( - 2 + 5)/(9)


\\ \sf = (3)/(9)


\\ \sf = (1)/(3)

User Feuermurmel
by
5.2k points